Improving the ability of 3‐PG to model the water balance of forest plantations in contrasting environments. Issue 4 (7th September 2015) - Almeida, Auro C.; Sands, Peter J.
Abstract: Because water availability is a primary factor that influences growth of forest plantations, quantifying plantation water use is an important part of the decision‐making process when selecting new plantation areas. The 3‐PG model (Landsberg and Waring, Forest Ecology and Management 95: 209–228, 1997) has been used successfully to model forest growth for several species. However, some studies have demonstrated limitations in 3‐PG's ability to accurately model the soil and plant water balance. This paper addresses these limitations through the development and validation of a modified water balance submodel that models canopy interception, soil evaporation, tree transpiration, drainage, run‐off, soil water content and available soil water in the root and non‐root zone. The new submodel was tested and validated using detailed, long‐term observed growth and water balance data from contrasting environments in Australia and Brazil and showed improved estimation of available soil water, even when only monthly weather data were available. However, the new submodel requires more soil texture‐dependent parameters than the original submodel. Sensitivity analysis of these new parameters shows that values of soil field capacity, wilting point and soil depth may have strong impacts on the prediction of run‐off, soil water content and available soil water. Copyright © 2015 John Wiley & Sons, Ltd.